Integrating market chain assessments with zoonoses risk analysis in two cross-border pig value chains in Lao PDR - Anna L. Okello (2018)
Copyright © 2017 by Asian-Australasian Journal of Animal Sciences. Objective: Lao PDR's recent accession to the World Trade Organization necessitates a greater understanding of the patterns and risk of livestock production in order to better align national policy with the Agreement on the Application of Sanitary and Phytosanitary Measures. This eco-health study was conducted to improve understanding of the interrelations between market chains and zoonotic infection risks at two strategic cross border points between Lao PDR, Thailand and Viet Nam. Methods: Information gained from smallholder farmer/trader interviews was integrated with serological surveys for pig-associated zoonoses-including hepatitis E virus (HEV), Taenia solium (T. solium) and trichinella-to identify potential linkages between disease risk and pig production and slaughter in low input systems common across the country. Results: Trichinella and HEV exposure was high in both humans and pigs in both study areas, significantly associated with pig slaughter and the subsequent consumption and handling of raw pork products. T. solium demonstrated a strong geographical and ethnic association with the northern study area bordering Vietnam. With the right knowledge and accessible, affordable inputs, the majority of smallholder farmers indicated a willingness to invest more in pig production, which could simultaneously improve livelihoods and decrease exposure to HEV, Trichinella, and T. solium through increased access to formal markets and an improved slaughter processes. Conclusion: The linkages identified when assessing disease risk in the context of potential economic and cultural drivers of transmission highlight the importance of a systems-based approach for the detection and control of zoonotic disease, and contributes to an improved understanding of the Lao PDR livestock sector.